A trajetória profissional e a prática docente de Nini Paes de Araújo em Itabaiana/PB (1945 -1988) - Santos, Enoque Bernardo (2021)
Nini Paes de Araújo graduated as a primary teacher at Escola de Professores do Instituto de Educação da Paraíba, under the auspices of the Scholanovism, but before that she studied at Colégio Nossa Senhora das Neves, both of them in the capital of Paraíba, where she acquired a whole Catholic cultural repertoire. This thesis, in the field of History of Education, aims to study the teaching practice of NiniPaes de Araújo, in Itabaiana/PB, and the guiding question of this research is: How did Professor Nini Paes de Araújo articulate in her teaching practice the Catholic cultural repertoire, which she obtained along with the experience working together with the Holy Family Sisters, and the ideas of Scholanovismacquired during his formation as a primary teacher at Escola de Professores? In this sense, our goal is to investigate whether the teaching practice of Nini Paes de Araújo was permeated by the Catholic pedagogical repertoire experienced at Colégio Nossa Senhora das Neves or by the scholovist ideas of the Escola de Professores do Instituto de Educação Secundária da Paraíba, between 1945 to 1988, that includes the period in which she practiced teaching. This research is based on the perspective of the New Cultural History and inserted in the biographical modality, with contributions of Oral History Methodology, conduct of interviews with ex-students of Nini Paes de Araújo, in order to identify through the testimonies as there was the teaching practice of the subject under study, in two educational establishments in Itabaiana: Escola Normal Regional Nossa Senhora da Conceição and Colégio Estadual of Itabaiana. The access to memory by interview, boosted the search, knowledge and analysis of a range of other sources, such as: handwritten memories, iconographic sources, school notebooks, and the teacher's personal documents; messages from Executive of Paraíba; Papal Encyclicals, namely Pope Leo XIII and Pope Pius XI; besides the journals such as: A União, A Imprensa, A Folha, Revista de Ensino da Paraíba, Diário de Pernambuco and Correio da Paraíba.The reading and analysis of the sources indicate that the pedagogical practice of NiniPaes de Araújo was based on the Christian orientations of the Sacred Family Sistersat Colégio Nossa Senhora da Neves, considering that she spent seven years in this institution and, due that experience, she appropriated the conservative catholic speech, using it in and outside the school rooms, in order to demonstrate her position as a Catholic woman and teacher, with regard to education and politics. Perceptible positioning by her ex students from both educational establishments where the subject of our research has taught. Thus, Nini Paes de Araújo demonstrated that her pedagogical practice was interconnected with her Catholic believes.